2014
DOI: 10.1016/j.jphys.2013.12.003
|View full text |Cite
|
Sign up to set email alerts
|

Some physiotherapy treatments may relieve menstrual pain in women with primary dysmenorrhea: a systematic review

Abstract: Physiotherapists could consider using heat, transcutaneous electrical nerve stimulation, and yoga in the management of primary dysmenorrhea. While benefits were also identified for acupuncture and acupressure in no-treatment controlled trials, the absence of significant effects in sham-controlled trials suggests these effects are mainly attributable to placebo effects.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
72
0
19

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 169 publications
(108 citation statements)
references
References 26 publications
2
72
0
19
Order By: Relevance
“…The results of the current study were also in agreement with those of the above-mentioned studies, especially a systematic review performed by Kannan and Claydon showed the statistically significant reduction in pain severity due to several physiotherapy interventions such as using heat, transcutaneous electrical nerve stimulation, and yoga (30).…”
Section: Discussionsupporting
confidence: 91%
“…The results of the current study were also in agreement with those of the above-mentioned studies, especially a systematic review performed by Kannan and Claydon showed the statistically significant reduction in pain severity due to several physiotherapy interventions such as using heat, transcutaneous electrical nerve stimulation, and yoga (30).…”
Section: Discussionsupporting
confidence: 91%
“…Possibly useful methods: traditional Chinese herbal medicine, acupuncture and acupressure, moxibustion, omega-3 fatty acids, vitamin B1, vitamin E, magnesium, exercise, yoga, chaste tree, yarrow, toki-shakuyaku-san -Kampo medicine from Japan, cinnamon [81,[86][87][88][89][90][91][92][93][94][95]. Probably sound means: aroma oil massage (lavender oil, rose oil), and the inhalation of lavender scent or fragrance saffron treatment [96][97][98][99].…”
Section: Apitherapeutic Recommendations For the Treatment Of Primary mentioning
confidence: 99%
“…Probably sound means: aroma oil massage (lavender oil, rose oil), and the inhalation of lavender scent or fragrance saffron treatment [96][97][98][99]. Demonstrably sound means: local heat application, transcutaneous electrical nerve stimulation, and ginger [81,92,100,101].…”
Section: Apitherapeutic Recommendations For the Treatment Of Primary mentioning
confidence: 99%
“…A recent systematic review [22] that evaluated the efficacy of physiotherapy interventions for PD identified a single RCT on exercise [18]; however, the RCT was not eligible for the review as pain was not an outcome measure in the study. A review in 2008 [11] and a Cochrane systematic review of RCTs in 2010 [23] on exercise for PD identified only a single RCT on exercise for PD [18], with major methodological flaws.…”
Section: Introductionmentioning
confidence: 99%